The analysis of domestic tourism potentials in relation to global trends and the importance for economic development of Serbia - Bogetić, Srdjan; Bešić, Cariša; Đorđević, Dejan (Hotel and Tourism Management, 2017)
New competitive relations require new approaches in the field of organizational management and development of competitiveness. In the environment characterised by global market changes, hotel enterprises have to adjust in order to survive on the market and satisfy their end users needs. Domestic hotel enterprises have to accept new market trends, adapting, in this way, to the end users? requirements. In order to make domestic hotel enterprises competitive internationally, it is necessary to change their way of thinking and, in some time, to adopt modern world achievements in the sphere of organisational management.